2006
DOI: 10.1002/jat.1157
|View full text |Cite
|
Sign up to set email alerts
|

Benzo(a)pyrene‐induced acute neurotoxicity in the F‐344 rat: role of oxidative stress

Abstract: Given the link between neurotoxicity and exposure to pollutants, the potential behavioral neurotoxicity of benzo(a)pyrene [B(a)P] was investigated. Studies have established that B(a)P requires metabolic activation to highly reactive species to elicit many of its adverse effects. This study investigated the perturbation of nervous system function by correlating behavioral changes with the metabolism of B(a)P, antioxidant enzyme levels and lipid peroxidation in selected brain regions. The neurobehavioral effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
129
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(134 citation statements)
references
References 57 publications
4
129
1
Order By: Relevance
“…Studies have shown that PAHs and organochlorine pesticides could induce oxidative stress (29)(30)(31)(32)(33). Oxidative stress has long been considered to be a mechanism of teratogenic action for many compounds, resulting in the misregulation of redox-sensitive signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that PAHs and organochlorine pesticides could induce oxidative stress (29)(30)(31)(32)(33). Oxidative stress has long been considered to be a mechanism of teratogenic action for many compounds, resulting in the misregulation of redox-sensitive signal transduction pathways.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Laboratory studies in experimental animals have revealed neurodevelopmental and behavioral effects of PAH exposure during the prenatal and neonatal periods, including anxiety, depressionlike symptoms, and memory impairment. [20][21][22][23][24][25][26] Our previous research in a New York City birth cohort and in the present Krakow birth cohort revealed that prenatal exposure to PAH was associated with adverse cognitive outcomes at age 5 years 27,28 and with behavioral problems, including anxiety and depression, at ages 6 to 7 years in New York City. 29 Although there is some previous human evidence of interactions between socioeconomic factors and pollutants, [30][31][32][33][34] this is the first study assessing the interaction of PAHs and maternal psychological distress on neurobehavioral outcomes.…”
mentioning
confidence: 96%
“…The brain is also characterized by relatively low levels of anti-oxidative enzymes (Reiter, 1995;Escames et al, 1997;Esparza et al, 2005). Moreover, both investigated substances: exogenous melatonin and B(a)P readily cross a blood-brain barrier and reach the brain in a clinical relevant concentrations (Menendez-Pelaez et al, 1993;Moir et al, 1998;Saunders et al, 2006;Reiter et al, 2008;Zhang et al, 2008). The liver was included because of its multiple detoxication pathway including during B(a)P intoxication.…”
Section: Accepted M M a N U mentioning
confidence: 99%
“…B(a)P crosses a blood-brain barrier and induces acute neurobehavioral toxicity through oxidative stress due to inhibition of the brain antioxidant scavenging system (Moir et al 1998;Saunders et al, 2006;Zhang et al, 2008). Generation of oxygen-based reactive molecules in brain can increase permeability of the blood-brain barrier and modify synaptic transmission (Evans, 1995).…”
Section: Accepted M M a N U mentioning
confidence: 99%